Textbook still useful in the covid-19 era: Investigation perceptions of students at the university - Heriansyah; Setiawan, Edi; Jumareng, Hasanuddin; Saman, Abdul; Gani, Ruslan Abdul (Journal Sport Area, 2022)
The COVID-19 era presents many obstacles for students to study and gain knowledge about physical education, so it is necessary to use textbooks thus enabling them to master the subject matter more optimally. The purpose of this study was to determine student perceptions at the university level about physical education learning model textbooks during COVID-19. This research uses mixed methods. Twenty five subjects from sports students at Halu Oleo University are willing to contribute to this research. Quantitative data collection techniques are through questionnaires while qualitative data collection is through in-depth interviews. The results of the research quantitatively found that most of the subjects had a very agreeable perception of the use of textbooks in the COVID-19 era. While the results of qualitative research indicate that the majority of subjects give the perception that physical education learning model textbooks have quality material content, use of language and good design. In addition, they consider that physical education learning model textbooks are pedagogical tools that have many benefits when used during the COVID-19 pandemic, one of which is to increase knowledge. Therefore, one of the efforts that can be made so that sports students have the willingness to learn during the COVID-19 pandemic is to provide quality textbooks.